(untitled) (Torani Journal of Fisheries and Marine Science, 2017)
Fisheries management requires reliable estimation and can be made as a consequence of the alternatives strategy exploitation, it requires knowledge about the biological condition of the fish stocks at a certain time, one of them is a grouper (Plectropomus leopardus).The aims of this study is to analyze the biological diversity includes the average total length, size structure and weight-length relationship of groupers (Plectropomus leopardus) in Spermonde Islands. The results are expected to provide information on sustainable resource management in Spermonde Archipelago.The study was conducted from July 2013- February 2014 in three locations of Spermonde archipelago,namely Sarappo Island, LumulumuIsland and LangkaiIsland using primary data. Research methods such as measurement of total length and weight of the grouper Sunufish from the catch of fishermen and traders in each collection area. The average of the total length, the size structure and weight length relationships were analyzed descriptively,The analysis results of the average total length of the grouper (P. leopardus) caught in Sarappo Island, Lumulumu Island and Langkai Island respectively 29.84 ± 8.6 cm (N = 624), 31.93 ± 8.03 cm ( N = 291), 34.64 ± 7.41 cm (N = 214) where the nearer them to the mainland,the smaller averagetotal length is. The size distribution of grouper sunu (P. leopardus) in the Sarappo island and Lumulumu island are most of the small size which is 22.5 cm by 35.63% and 22.68%, and on the Langkai island the most caught fishes size are 37.5 cm by 31, 77%. Weight-length relationship on the three islands are minor allometric, Keywords: total length, structure size, weight length relationship, grouper Spermonde Archipelago